Construction and validation of a data collection instrument for nursing care during prehospital mobile assistance to trauma victims - Cyrillo, Regilene Molina Zacareli; Dalri, Maria Célia Barcellos; Cristina, Jane Aparecida (Rev Rene, 2005)
The lack of references to the nursing process to trauma victims during Pre-hospital Mobile Assistance motivated us to construct a data collection instrument as an initial step in the nursing process. We used Horta’s conceptual model and the mnemonic method of ATLS to rank care priorities. The instrument was constructed as a check-list form, to be applied in a Microsoft Access database. Validation was realized by specialists in this area and, after analysis, some changes were suggested and carried out to adapt the instrument to practical use. We hope to offer the conditions to document and qualify nursing care and to lead nurses towards professional identity and respect.